PENGELOLAAN DAN PENGOLAHAN SAMPAH PADA MASYARAKAT SEKITAR KAMPUS 2 UNAND, PAYAKUMBUH - Bintang Rizky Abdullah Majo Saibah; Winny Alna Marlina; Ranny Fitriana Faisal; Agestayani Agestayani; Erizal Erizal; Susiana Susiana; Musbatiq Srivani; Faisal Ali Ahmad; Jauharry Jauharry (LPPM Universitas Andalas, 2018)
Environmental, economic and social aspects are three important pillars in sustainable development. However, the 2017 West Sumatra Environmental Management Regional Performance Document (DIKPLHD) stated that the waste generation in West Sumatra reached 2,452,213 kg / day and only 34.54% of districts / cities had managed the waste properly. So far, the handling of waste is usually conducted by stacking, collecting, and transporting to the Final Processing Site (TPA). Therefore, it is important to start a systematic program to reduce waste. One possible method that can be implemented is the empowerment of the waste bank. Campus 2 UNAND Payakumbuh has conducted community service through socialization and training programs with the theme